2017
DOI: 10.1159/000481413
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Segmental Colectomy Followed by Endoscopic Surveillance as a Treatment Strategy for Colorectal Cancer Patients with Lynch Syndrome

Abstract: Background: Initial surgical procedures for colorectal cancer (CRC) patients with Lynch syndrome remain controversial. This study assessed the validity of segmental colectomy (SGC) followed by endoscopic surveillance as a treatment strategy for CRC patients with Lynch syndrome. Methods: Among consecutive patients who underwent surgery for primary CRC between April 1985 and December 2014, 49 patients were observed to have germline mutations in a mismatch repair gene, and 38 patients who underwent SGC followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For these reasons, extended surgery as a surgical procedure for newly diagnosed colorectal cancer in patients with Lynch syndrome is recommended with the objective of securely reducing the risk of metachronous colorectal cancer development [ 236 ]. Meanwhile, a study indicated that there were no differences in mortality rate between the two groups (relative risk of segmental resection, 1.65 [95% CI 0.90–3.02)] [ 271 ], but there has been insufficient discussion on this, and data relating to surgical procedures for newly diagnosed colorectal cancer in Japan are minimal [ 66 , 272 ].…”
Section: Commentsmentioning
confidence: 99%
“…For these reasons, extended surgery as a surgical procedure for newly diagnosed colorectal cancer in patients with Lynch syndrome is recommended with the objective of securely reducing the risk of metachronous colorectal cancer development [ 236 ]. Meanwhile, a study indicated that there were no differences in mortality rate between the two groups (relative risk of segmental resection, 1.65 [95% CI 0.90–3.02)] [ 271 ], but there has been insufficient discussion on this, and data relating to surgical procedures for newly diagnosed colorectal cancer in Japan are minimal [ 66 , 272 ].…”
Section: Commentsmentioning
confidence: 99%